REGIONAL TOURISM IN RUSSIA: MODERN STATE AND WAYS OF DEVELOPMENT - Z. Musaeva (Вестник университета)
The article is devoted to revealing the specifics of regional tourism in Russia. The article also presents the features of Russian tourism and examines the factors affecting regional tourism in the regional economy and the economy of the country as a whole, which is the relevance of the issue under study. Special attention is paid to the analysis of indicators in the region and the Republic in particular for the three reporting periods. This article provides a list of activities that will help to develop tourism in the country.